Examining The Impact of Social Media Networks on Information Sharing Among The Students of Kabale University. - Tokamanya, Jonas (Kabale University, 2024)
This study assessed the impact of social media networks on Information sharing among the students of Kabale University. A descriptive cross-section study. Self-administered questionnaires and interview guides were used in data collection and data was analyzed using Excel, a computer software to generate descriptive statistics such as frequencies and percentages, and were presented in tables and text. The sampling techniques used were simple random sampling and purposive sampling. The objectives of the study were to identify the different forms of social media used by students, to investigate the influence of social media on information sharing among students, to examine the challenges faced in using social media in information sharing, and to suggest possible strategies to reduce the challenges of social media in information sharing among students of Kabale University and a sample size of 50 respondents was selected for the study. The study findings on different forms of social media used by students of Kabale University the results presented show that the highest number of the respondents mentioned Facebook. In contrast, the least number of the respondents mentioned Twitter, as the influence of social media on information sharing of students of Kabale University, the highest number of respondents mentioned that it leads to the sharing of useful information, the lowest number of respondents said that technological communication harms interpersonal skills. The challenges faced in using social media in information sharing among students of Kabale University were that the highest number of respondents mentioned resource challenges and the lowest number of respondents talked of attitude challenges.